Workplaces as learning spaces - conceptual and empirical insights - Ostendorf, Annette; Permpoonwiwat, Chompoonuh K. (Conference series, 2017)
This volume is focused on workplaces as learning spaces. It is the fourth volume of Asian and European researchers carrying out common or related work in the field of workplace learning. They are organised in the ASEM Lifelong Learning research net-work, which was established in 2005 and includes members from 14 countries in Asia and Europe. The research network is enhancing a vivid exchange of knowledge and ideas on workplace learning across different countries, cultures and continents and it conducts research agreed on common concepts. The contributions in this volume comprise in many cases empirical data gained by combining different qualitative re-search methods, including visual methods. The work of all researchers and research teams in this paper collection is dedicated to throw light on the phenomenon of work-places as learning spaces, and to explain different facets of meaning, processes and structure related to it. - Dieser Band konzentriert sich auf Arbeitsplätze als Lernräume. Es ist der vierte Band von asiatischen und europäischen Forschern/innen, die gemeinsame oder aufeinander bezogene Arbeiten auf dem Gebiet des Lernens am Arbeitsplatz durchführen. Sie sind im ASEM-Forschungsnetzwerk für lebenslanges Lernen organisiert, das 2005 gegründet wurde und Mitglieder aus 14 Ländern in Asien und Europa umfasst. Das Forschungsnetzwerk fördert einen lebendigen Austausch von Wissen und Ideen zum Lernen am Arbeitsplatz über verschiedene Länder, Kulturen und Kontinente hinweg und führt Forschungsarbeiten durch, die auf gemeinsamen konzeptionellen Grundlagen basieren. Die Beiträge in diesem Band umfassen in vielen Fällen empirische Daten, die durch die Kombination verschiedener qualitativer Forschungsmethoden, einschließlich visueller Methoden, gewonnen wurden. Die Arbeit aller Forscher/innen und Forschungsteams in diesem Sammelband ist darauf ausgerichtet, das Phänomen des Arbeitsplatzes als Lernraum zu beleuchten und verschiedene Facetten der damit verbundenen Bedeutung, Prozesse und Strukturen zu erklären.